2017
DOI: 10.1148/rg.2017160162
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Approach to Intra-abdominal Adverse Effects of Targeted Cancer Therapies

Abstract: Targeted cancer therapies encompass an exponentially growing number of agents that involve a myriad of molecular pathways. To excel within this rapidly changing field of clinical oncology, radiologists must eschew traditional organ system-based approaches of cataloging adverse effects in favor of a conceptual framework that incorporates molecular mechanisms and associated clinical outcomes. Understanding molecular mechanisms that underlie imaging manifestations of adverse effects and known associations with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 92 publications
(146 reference statements)
0
7
0
Order By: Relevance
“…We believe that the clinical course of our patient indicates that pazopanib plays an important role in the development of intestinal lymphangiectasia. A review of molecularly targeted drugs showed the possible development of intestinal lymphangiectasia in patients taking pazopanib or axitinib [5]. Pazopanib is a multikinase inhibitor with VEGFR, platelet-derived growth factor receptor, and Kit as its target molecules, and these effects may have caused the development of intestinal lymphangiectasia in the present case.…”
Section: Discussionmentioning
confidence: 76%
“…We believe that the clinical course of our patient indicates that pazopanib plays an important role in the development of intestinal lymphangiectasia. A review of molecularly targeted drugs showed the possible development of intestinal lymphangiectasia in patients taking pazopanib or axitinib [5]. Pazopanib is a multikinase inhibitor with VEGFR, platelet-derived growth factor receptor, and Kit as its target molecules, and these effects may have caused the development of intestinal lymphangiectasia in the present case.…”
Section: Discussionmentioning
confidence: 76%
“…SMF in patients treated with mtTKIs could possibly represent intestinal lymphangiectasia, a rare disease caused by either congenital abnormal lymphatic development or an acquired lymphatic obstruction. Lymphangiectasia in patients on antiangiogenic TKIs has been reported only once before, by Chang et al, 11 who suggested that intestinal lymphangiectasia in patients receiving VEGF TKIs may be related to VEGF's important role in lymphatic development, 20 and alterations in gene expression of VEGFR in patients with idiopathic intestinal lymphangiectasia. 21 In our study, small bowel was involved in 5/7 (71.4%) patients with positive SMF, slightly more frequent than the large bowel (3/7; 42.9%).…”
Section: Discussionmentioning
confidence: 97%
“…A literature search revealed only an annotation of this phenomenon, and no studies have previously assessed these findings and their association with TKI treatment. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted therapy based on suppression of specific genes or molecules contributing to malignant transformation and progression of tumor growth is a promising strategy to arrest cancer cells' division and spread. The main disadvantage of targeted therapy is ability to hit only one molecular target whereas a huge number of molecules and signaling pathways mediate malignant state of cells, and it also has serious side effects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%